Sarawak Technical and Vocational Educational Training Instructors : The Pursuit of Happiness and Psychological Detachment Across Sarawak Region - Dayang Khairunnisa, Awang Ahmad; Zaiton, Hassan; Sheilla Lim, Omar Lim (Perkama International Persatuan Kaunseling Malaysia Antarabangsa, Kajang, Selangor, 2022)
The study aims to identify the relationship between psychological detachment (i.e., relaxation, mastery, and control of experience) and happiness in the workplace among Technical and Vocational Education Training (TVET) instructors from various TVET institutions across the Sarawak region. Electronic survey was completed by 122 TVET instructors. Pearson correlation coefficient analysis was used, and overall, the findings showed that the TVET instructors' psychological detachment had a significant relationship with their happiness in the workplace. Multiple linear regression was used to further examine the associations between predictor and outcome variables, with control of experience mostly contributed to the TVET instructors' happiness in the workplace. Thus, it is suggested that TVET institution should strategically create leisure areas at the workplace for the instructors to relax during their off-work hours, provide skills training, and allow them to have control over their own leisure time can increase their happiness in the workplace.